Tendon‐derived progenitor cells improve healing of collagenase‐induced flexor tendinitis. Issue 12 (7th April 2016) - Durgam, Sushmitha S.; Stewart, Allison A.; Sivaguru, Mayandi; Wagoner Johnson, Amy J.; Stewart, Matthew C.
ABSTRACT: Tendinitis is a common and a performance‐limiting injury in athletes. This study describes the value of intralesional tendon‐derived progenitor cell (TDPC) injections in equine flexor tendinitis. Collagenase‐induced tendinitis was created in both front superficial digital flexor (SDF) tendons. Four weeks later, the forelimb tendon lesions were treated with 1 × 10 7 autogenous TDPCs or saline. Tendinitis was also induced by collagenase in one hind SDF tendon, to study the survival and distribution of DiI‐labeled TDPCs 1, 2, 4, and 6 weeks after injection. The remaining normal tendon was used as a "control." Twelve weeks after forelimb TDPC injections, tendons were harvested for assessment of matrix gene expression, biochemical, biomechanical, and histological characteristics. DiI‐labeled TDPCs were abundant 1 week after injection but gradually declined over time and were undetectable after 6 weeks. Twelve weeks after TDPC injection, collagens I and III, COMP and tenomodulin mRNA levels were similar ( p  = 0.3) in both TDPC and saline groups and higher ( p  < 0.05) than normal tendon. Yield and maximal stresses of the TDPC group were significantly greater ( p  = 0.005) than the saline group's and similar ( p  = 0.6) to normal tendon. However, the elastic modulus of the TDPC and saline groups were not significantly different ( p  = 0.32). Histological assessment of the repair tissues with Fourier transform‐second harmonic generation imaging demonstrated that collagen alignment was significantly better ( p  = 0.02) in TDPC group than in the saline controls. In summary, treating collagenase‐induced flexor tendon lesions with TDPCs improved the tensile strength and collagen fiber alignment of the repair tissue. Study Design © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:2162–2171, 2016.